Educational Policy Transformation in Indonesia: From the Old Order to the Reform Era - Sugiarto Sugiarto; Fathur Rokhman; Eko Handoyo (STIT Ahlussunnah Bukittinggi, 2026)
Education is a strategic instrument in national development, playing a vital role in improving human resource quality, strengthening national identity, and promoting economic growth. In the Indonesian context, educational policies have undergone significant transformations influenced by political regime changes from the Old Order, New Order, and Reform Era. This study aims to analyze the transformation of educational policies in Indonesia across these three periods. The study employed a qualitative method using a content analysis approach to examine various regulations, policy documents, and relevant academic literature. The findings reveal that educational policies during the Old Order were primarily oriented toward ideological formation and national identity building, while those of the New Order focused on national development through a centralized education system. In contrast, educational policies during the Reform Era emphasized decentralization, democratization, and increased public participation in educational governance. The study further demonstrates that political transitions have significantly influenced the direction and characteristics of national educational policies. Despite various policy reforms, their implementation continues to face challenges, including regulatory inconsistencies, weak policy execution, and gaps between policy formulation and educational practice. Therefore, more consistent, evidence-based educational policies supported by effective governance are required to enhance educational quality sustainably and respond adaptively to global challenges.